Effects of Paraffin Emulsion on the Structure and Properties of Soy Protein Films. Issue 9 (1st September 2016) - Liu, X.; Yu, M.
Abstract : In this work, the water-repellent capacity of the paraffin emulsion−covered soy flour (SF) substrate has been studied. Effect of paraffin emulsion content on the structure and properties of the resulting films were studied using laser particle size distribution analyzer, water absorption test, x-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), and tensile testing. Study on the emulsion particle size and stability revealed that the particle size distribution and stability were strongly dependent on the pH of the system. And the optimum pH was 9.9. The incorporation of paraffin emulsion produced at pH 9.9 could markedly enhance the water resistance of films. However, the improvement was realized at the expense of decreased thermal stability and tensile strength of SF−paraffin emulsion films. The addition of paraffin emulsion could destroy the crystalline domains of soy protein and change the protein secondary structure. GRAPHICAL ABSTRACT: